2011
DOI: 10.1177/0194599811425140
|View full text |Cite
|
Sign up to set email alerts
|

Acute Mediastinitis Associated with Foreign Body Erosion from the Hypopharynx and Esophagus

Abstract: Delay in initiating treatment and intrathoracic esophageal foreign bodies are the main risk factors of mediastinitis secondary to foreign body ingestion. Computed tomography plays an important role in diagnosis and guiding treatments. In conjunction with aggressive surgical debridement and drainage, endoscopic stent placement could be the optimal management for most patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…Computed tomography (CT) is much more sensitive in the detection of any kind of foreign bodies prior to endoscopic interventions than plain radiographies. Importantly, the role of CT scan is not only to localize esophageal foreign bodies but also to evaluate relevant regional complications such as perforation, fistulization, and even pleural empyema [ 22 ]. Zhu et al reported that a more advanced dual source CT can even elevate the sensitivity and specificity to near 100% of diagnosis and evaluation of esophageal foreign bodies violently [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Computed tomography (CT) is much more sensitive in the detection of any kind of foreign bodies prior to endoscopic interventions than plain radiographies. Importantly, the role of CT scan is not only to localize esophageal foreign bodies but also to evaluate relevant regional complications such as perforation, fistulization, and even pleural empyema [ 22 ]. Zhu et al reported that a more advanced dual source CT can even elevate the sensitivity and specificity to near 100% of diagnosis and evaluation of esophageal foreign bodies violently [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…[4] The role of CT scanning does not aim to localize esophageal foreign bodies only, but also to evaluate relevant local complications including perforation, fistulization, and pleural empyema. [13] In our study, 14 (58.3%) patients had undergone cervical and lung X-rays before endoscopic intervention. FBs were detected in 4 (16.7%) patients through X-ray (Figure 4).…”
Section: Discussionmentioning
confidence: 74%
“…With the intention of using a flap for esophageal repair, intercostal muscle flap should be harvested before placing a rib spreader to avoid traumatizing vascular pedicle. The role of buttress technique was confirmed by several authors and that has definitely improved the outcome of the surgical treatment and reinforcement with vascularized tissue decreases the fistula formation (13%) and mortality (6%), compared to repair without reinforcement (39%) and (25%) [2,14,12,20]. Besides, there are various other local tissues at the site of perforation have been used to buttress the primary repair, such as pleural flaps, omental flaps, diaphragm and pericardial flaps, etc.…”
Section: Discussionmentioning
confidence: 97%